Oleogels based on Vegetable Oil and Synthetic Oil: Evaluation of the Effect of the Bentone on Gelling using a Mixture Design - Bennani, Ismail (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Oleogels are semisolid systems consisting on a lipophilic liquid phase with a gelling agent. Aim: The aim of our study is to demonstrate how the concentration of Bentone modifies the viscosity of the preparation as well as the influence of the polar activator included in the composition of the formulas. Moreover, this study aims to find the most appropriate formulation from the results obtained using a mixture design. Settings and Design: To define the formulation space for the oil viscosity, we tested an experimental design using software Design-ExpertÂ®. Subjects and Methods: In our study, a design of experiments approach was tested using a mixture design to evaluate the effects of Bentone and ethanol on enhancing viscosity using two categories of oils: Natural vegetables oils and synthetic oils. This viscosity was established by sensory analysis which resulted in a score on a scale from 0 to10. Statistical Analysis Used: The statistical significance of the model has been evaluated by using the analysis of variance. Results: The results showed a significant increase in the viscosity. The analysis of the design space showed that the viscosity of different oils varies very closely with the concentration of bentone. Formulation of oleogel based on bentone as gelling agent and oils seems to improve the viscosity of the formula. Conclusion: The mixture experimental design indicates clearly that the concentration of bentone determines the viscosity of the studied oils. The influence of variable concentration is a key factor to define conditions to have adequate viscosity.